ALGORITHM FOR ASSESING SOIL REHABILITATION OF STERILE DUMPS - BRASOVAN, Andreea; BURTESCU, Ramona Flavia; OLAH, Neli-Kinga; PETEAN, Ioan; CODREA, Vlad Aurel; BURTESCU, Andrei Bucurel (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Ileana Veche is the most representative waste rock (sterile) dump formed by the coal mining activities in Lupeni (Petroşani Basin). We developed an algorithm based on the computational engineering concepts in order to establish the connection between the waste rock soil particles composition and the dump rehabilitation by Scots Pine (Pinus sylvestris). The results show that the Ileana Veche pit coal dump features minerals suitable for plants growth like: calcite, biotite, potassium feldspar and chemically inert one as quartz. The quantitative measurements prove that the soil minerals are enough to allow a fair growing of the P. sylvestris population able to start the soil type conversion from the entiantrosoil type to a more fertile one. The measurements found that the upper soil presents humus formation and features nitrogen and phosphorous while these elements are missing in the deeper layer.